Biases in biodiversity: wide-ranging species are discovered first in the deep sea - Higgs, Nicholas D.; Attrill, Martin (Frontiers in Marine Science, 2015)
Calculating global estimates for total species richness is fraught by the uncertainty in estimating the number of species left to be discovered. The deep-sea is widely regarded as one of the largest sources of uncertainty in these calculations, since so much of this realm has not yet been explored. Most estimates of species left to be discovered are reliant on previous rates of species description, yet these rates are likely to be biased. One well known bias from terrestrial studies is that wide-ranging species tend to be described earlier. To test this hypothesis for the deep sea, spatial data from the Ocean Biogeographic Information System were combined with taxonomic data from the World Register of Marine Species to carry out a meta-analysis on all species records found below 300 m. Results show a historical bias in species descriptions, with wide-ranging species over-represented in our current catalogues of deep-sea species richness. This suggests that current estimates of deep-sea species richness underestimate the true proportion of narrow-ranged species and hence total species in the deep oceans.